Listening to Grass-Hoppers : Field Notes on Democracy - Roy, Arundhati (Rawalpindi Services Book Club, 2011)
With special reference to various topics related to anti-democratic issue of communalism, division between Muslims and Hindus, state sponsored terrorism, terrorist attacks, and emergence of Hindutva in India; articles previously published in several journals and books.
Include Maps and Index
Keywords: India -- Politics and Government -- Democracy -- Terrorism